2022
DOI: 10.3389/fgene.2022.969476
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive pancancer analysis reveals the potential value of RAR-related orphan receptor C (RORC) for cancer immunotherapy

Abstract: Background: RAR-related orphan receptor C (RORC) plays an important role in autoimmune responses and inflammation. However, its function in cancer immunity is still unclear. Its potential value in cancer immunotherapy (CIT) needs to be further studied.Methods: Expression and clinical data for 33 cancers were obtained from UCSC-Xena. The correlation between RORC expression and clinical parameters was analyzed using the limma software package to assess the prognostic value of RORC. Timer2.0 and DriverDBv3 were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…S5B). Given that RORC has previously been associated with immune cell infiltration in TETs [ 39 ] and that MTA3 has previously been implicated in immune response regulation [ 19 22 ], we focused on the role of MTA3 in TETs. We found that MTA3 was significantly downregulated in thymic tumors (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S5B). Given that RORC has previously been associated with immune cell infiltration in TETs [ 39 ] and that MTA3 has previously been implicated in immune response regulation [ 19 22 ], we focused on the role of MTA3 in TETs. We found that MTA3 was significantly downregulated in thymic tumors (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study has shown that the neuropeptide nociceptin/orphanin' FQ (N/OFQ) has been identified as a promising immunomodulator for inflammatory bowel diseases [37]. RORC, the core genes of the circadian clock, is a critical transcription factor for Th17 polarization and function, and it plays a significant role in autoimmunity and inflammation [38,39]. It is proved that RORC mRNA expression was increased in patients with UC [40,79].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that the neuropeptide nociceptin/orphanin' FQ (N/OFQ) has been identi ed as a promising immunomodulator for in ammatory bowel diseases (34). RORC is a critical transcription factor for Th17 polarization and function, and it plays a signi cant role in autoimmunity and in ammation (35). It is proved that RORC mRNA expression was increased in patients with UC(36).…”
Section: Discussionmentioning
confidence: 99%